Elucidation of Nitrate Reduction Mechanisms on a Pd‐In Bimetallic Catalyst using Isotope Labeled Nitrogen Species. Issue 1 (23rd November 2012) - Zhang, Rui; Shuai, Danmeng; Guy, Kathryn A.; Shapley, John R.; Strathmann, Timothy J.; Werth, Charles J.
Abstract To understand nitrate reduction pathway and to improve selectivity towards dinitrogen (N2) over toxic ammonia species (NH4+, NH3), aqueous reduction experiments with an Al2O3‐supported Pd‐In bimetallic catalyst were conducted by using isotope‐labeled nitrite (15NO2−). Nitrite is the first reduction intermediate of nitrate. Experiments were performed using nitrite alone and in combination with unlabeled proposed reduction intermediates (N2O, NO), and using only N2O and NO alone, each as a starting reactant. Use of 15N‐labeled species eliminates interference from ambient N2 when assessing mass balances and product distributions. Simultaneous catalytic reduction of 15NO2− and 14N2O shows no isotope mixing in the final N2 product, demonstrating that N2O does not react with other NO2− reduction intermediates; N2O reduction alone yielded only N2. In contrast, simultaneous catalytic reduction of 15NO2− and 14NO yielded mixed‐labeled 15/14N2 (MW: 29), whereas reduction of 15NO alone yields a mixture N2 and NH4+, the ratio of which varies with initial 15NO concentration. These findings, along with those from a new kinetic model we propose, indicate that highly reactive adsorbed NO (NO*), or other unspecified adsorbed N species (Nads), is a key intermediate involved in determining final product selectivity.